Hubungan Kerapatan Mangrove terhadap Kepadatan Makrozoobenthos di Pesisir Desa Jaring Halus Kabupaten Langkat Sumatera Utara - Icha Andari Ritonga; Hasan Sitorus; Yoes Soemaryono (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2017)
Mangroves serve as a habitat organism aquatic, one of which is Macrozoobenthos. The abundance of Macrozoobenthos are very dependent on the power of tolerance to environmental changes. This research was aimed to analyzed density of Mangrove and how a relation with abundance of macrozoobenthos in the coastal village of Jaring Halus. This research is done in December 2016 to Januari 2017. The study used purposive random sampling method by taking and observation of mangrove vegetation, abundance of macrozoobenthos, and measurement of water quality parameters. Data analysis included analysis of mangrove vegetation, analysis of macrozoobenthos, analysis of water quality and analysis of the substrate. Found 11 species of mangrove with density at Station I 5.166 ind/ha, Station II 4.066 ind/ha and Station III 1.567 ind/ha. For macrozoobenthos found 16 species are the research site at Station I 249 ind/m2, Station II 167 ind/ m2 and Station III 147 ind/ m2. The Relationship of Mangrove’s Density and Macrozoobenthos Abundance in the coastal village of Jaring Halus indicated by the equation y = 0,0808x + 24,225 with R2 of 0,7526 and r = 0,867. And the Relationship of organic materials and Macrozoobenthos Abundance indicated by the equation y = 93,20 x – 323,8 with R2 of 0,776 and r = 0,881. From the result of data analysis relationship are very stong and real.Keywords : mangrove, macrozoobenthos, Jaring Halus Village, water quality